12p gain is predominantly observed in non-germinomatous germ cell tumors and identifies an unfavorable subgroup of central nervous system germ cell tumors. Issue 5 (26th October 2021) - Satomi, Kaishi; Takami, Hirokazu; Fukushima, Shintaro; Yamashita, Satoshi; Matsushita, Yuko; Nakazato, Yoichi; Suzuki, Tomonari; Tanaka, Shota; Mukasa, Akitake; Saito, Nobuhito; Kanamori, Masayuki; Kumabe, Toshihiro; et al.
Abstract: Background: Central nervous system (CNS) germ cell tumors (GCTs) are neoplasms predominantly arising in pediatric and young adult populations. While germinomas generally respond to chemotherapy and radiation, non-germinomatous GCTs (NGGCTs) require more intensive treatment. This study aimed to determine whether 12p gain could predict the prognosis of CNS GCTs. Methods: Eighty-two CNS GCTs were included in this study. The 12p gain was defined by an additional 12p in the background of potential polyploidy or polysomy. Cases were analyzed using an Illumina methylation 450K array for copy number investigations and validated by fluorescence in situ hybridization (FISH). Results: A 12p gain was found in 25-out-of-82 cases (30%) and was more frequent in NGGCTs (12% of germinoma cases and 50% of NGGCT cases), particularly in cases with malignant components, such as immature teratoma, yolk sac tumor, choriocarcinoma, and embryonal carcinoma. 12p gain and KIT mutation were mutually exclusive events. The presence of 12p gain correlated with shorter progression-free (PFS) and overall survival (OS) (10-year OS: 59% vs. 94%, with and without 12p gain, respectively, P = 0.0002), even with histology and tumor markers incorporated in the multivariate analysis. Among NGGCTs, 12p gain still had prognostic significance for PFS and OS (10-year OS: 47% vs. 90%, respectively, P = 0.02). The 12p copy number status was shared among histological components in mixed GCTs. Conclusions: 12p gain may predict the presence of malignant components of NGGCTs, and poor prognosis of the patients. It may be associated with early tumorigenesis of CNS GCT.